Ryan's dilemma - Vohra, Neharika, 1966- (SAGE Business Cases., 2018)
The case centers on Ryan Bansal, a recent business graduate, who attempts to affect change in his family business using the theoretical knowledge he acquired at University. The case illustrates the complexities of family business and the difficulties of implementing organizational change.